2007
DOI: 10.1021/jf062800k
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol Profiles ofVitis viniferaRed Grapes and Their Single-Cultivar Wines

Abstract: The main flavonols found in seven widespread Vitis vinifera red grape cultivars include the 3-glucosides and 3-glucuronides of myricetin and quercetin and the 3-glucosides of kaempferol and isorhamnetin. In addition, the methoxylated trisubstituted flavonols, laricitrin and syringetin, were predominantly found as 3-glucosides. As minority flavonols, the results suggest the detection of the 3-galactosides of kaempferol and laricitrin, the 3-glucuronide of kaempferol, and the 3-(6' '-acetyl)glucosides of quercet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
306
6
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(361 citation statements)
references
References 28 publications
32
306
6
1
Order By: Relevance
“…the increase of the band at 380 nm, is the most correlated to vinification time, probably contributing to the yellowish colour of the white wine. This confirm previous observation regarding the evolution of flavonols undergoing hydrolysis in the last stage of vinification (Castillo-Muñoz et al, 2007). Polyphenol extract spectra of the red wines (Cannonau and Cabernet) presented a band at 281 nm attributed to HBA, stilbenes and flavan-3-ols and to the UV absorbing part of the anthocyanin structures and a band at 371 nm, characteristic of flavonols (Hang & Wrolstad, 1990).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…the increase of the band at 380 nm, is the most correlated to vinification time, probably contributing to the yellowish colour of the white wine. This confirm previous observation regarding the evolution of flavonols undergoing hydrolysis in the last stage of vinification (Castillo-Muñoz et al, 2007). Polyphenol extract spectra of the red wines (Cannonau and Cabernet) presented a band at 281 nm attributed to HBA, stilbenes and flavan-3-ols and to the UV absorbing part of the anthocyanin structures and a band at 371 nm, characteristic of flavonols (Hang & Wrolstad, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…The presence in Vermentino of a broad band centered at around 350 nm ( Figure 1A), attributed to flavonols (mainly Kaempferol-and quercetin-type flavonols) depends on the maceration process where the skin of the berries, rich in flavonols, has been also used (see the 2.1 section), in accordance with the Sardinian winemaking tradition (Sanna et al, 2008;Castillo-Muñoz et al, 2007). Furthermore, the slight bathochromic shift of the flavonol band to 380 nm, previously described for sample V66, can be ascribed to the tendency, over time, of glycosylated flavonols to hydrolyze, thus changing the UV-Vis maxima (Castillo-Muñoz et al, 2007). PCA indicated that in the first weeks of vinification HBA, stilbenes and flavan-3-ols (band at 280 nm) increase significantly, together with flavonols.…”
Section: Discussionmentioning
confidence: 78%
“…Approximately 90% of the flavonols are hydroxylated in C3, C5 and C7, being designated as 3,5,7-trihydroxylated derivatives [18]. In grapes, there were identified: quercetin (3′,4′-diOH), kaempferol (4′-OH), myricetin (3′,4′,5′-triOH), isorhamnetin (3′-MeO analog of quercetin), laricitrin (3′-MeO analog of myricetin) and syringetin (3′,5′-MeO analog of myricetin) ( Figure 3II).…”
Section: Flavonoidsmentioning
confidence: 99%
“…To date, all glycosides of aroma compounds have been shown to include a direct linkage of the aroma compound to a β-d-glucose moiety (Winterhalter and Skouroumounis 1997). This is in contrast to other metabolites that may be linked to other sugars, such as the case of quercetin, which, in addition to a glucose, may also be glycosylated to glucuronic acid (Castillo-Muñoz et al 2007) (Figure 3). …”
Section: Structures Of Glycosidesmentioning
confidence: 99%